Investigation the Effect of Digital Taxation and Digital Accounting on Customs Efficiency and Port Sustainability - Omar M. Shubailat; Aziz Madi; Murad Ali Ahmad Al-Zaqeba; Khairil Faizal Khairi (Growing Science, 2024)
Indexed by Scopus